Smoking, 17 Alpha-Hydroxyprogesterone Caproate, and Preterm Birth - Heyborne, Kent D.; Allshouse, Amanda A. (American Journal of Perinatology, 2016)
Objective The objective of this study was to determine if maternal smoking modifies the effectiveness of 17 α-hydroxyprogesterone caproate (17OHP-C).Study Design Secondary analysis of the Maternal-Fetal Medicine Units Network trial of 17OHP-C. The prevalence of preterm birth (PTB) by smoking status and treatment group was compared by chi-squared analysis and analysis of variance was used to compare gestational age (GA) at birth. Multivariable modeling was used to estimate the effect of smoking on 17OHP-C treatment.Results In this study, 459 women were included. Maternal smoking significantly modified the effectiveness of 17OHP-C treatment. In smokers, 17OHP-C significantly reduced the prevalence of multiple outcomes (PTB < 37 and < 35 weeks, spontaneous PTB < 37 and < 35 weeks), while in nonsmokers, only PTB < 37 weeks was reduced. Delivery GA was later in 17OHP-C versus placebo treated smokers (36.4 vs. 34.3 weeks, p = 0.041) but not nonsmokers (36.3 vs. 35.5 weeks, p = nonsignificant). In multivariable modeling, 17OHP-C was more effective in smokers than nonsmokers as measured by multiple outcomes (PTB < 37 weeks [p = 0.041] and < 35 weeks [p = 0.036] and spontaneous PTB < 37 weeks [p = 0.029]).Conclusion In this cohort of women with a prior PTB, maternal smoking status significantly modified the effectiveness of 17OHP-C treatment.
Keywords: 17 α-hydroxyprogesterone caproate; 17OHP-C; smoking; preterm birth; progesterone; tobacco